Museum Preservation of Skeleton of Fetus & Small Vertebrates - Vina Ravi Vaswani2, Bindhu. S1, K. Leena Pramod1 (Recent Research in Science and Technology, 2011)
Transparency technique to demonstrate cartilage and skeleton has been used from years. It is superior to the method of obtaining fetal skeleton by boiling and burying, consisting basically of muscle digestion and staining of cartilage and skeleton. The process involves maceration of soft tissues in 1% KOH and staining of specimen using Alcian Blue 8GX and Alizarin Red S allowing detection of morphology of whole vertebral column and single vertebra, long bones and primary ossification centers. Keywords: Maceration, Alcian Blue, Alizarin Red S, KOH, Primary ossification centre, Fetal skeleton, Small vertebrate